Identity Politics Dynamics and the Construction of Electability of Legislative Candidates: A Phenomenological Study in Dapil II East Lombok in the 2024 Election - Lalu Moh. Nazar Fajri; Hapipi Jayadi; Silvia Hardiani; Ruli Ardiansyah (UIN Mataram, 2026)
This phenomenological study examines the dynamics of identity politics and electoral viability construction among legislative candidates in Electoral District II (Dapil II) of East Lombok during Indonesia's 2024 elections. Employing Alfred Schutz's phenomenological framework integrated with Social Identity Theory and political opportunity structure perspectives, the research explores how candidates strategically leverage multiple identity markers religious, ethnic, and regional to enhance electoral appeal. Through purposive sampling involving 15 legislative candidates and campaign team members, supplemented by ethnographic observation (60+ hours), discourse analysis of campaign materials, and textual interpretation of social media messaging, the study identifies three critical mechanisms of electability construction: (1) identity codification selective emphasis of specific identity dimensions while downplaying others; (2) constituency-identity alignment construction of authentic representation narratives; and (3) inter-candidate differentiation distinction through identity positioning. Findings reveal that identity politics operates simultaneously as structural constraint and agentic resource, wherein candidates experience identity mobilization not as pure strategy but as embedded within webs of authentic belief, moral judgment, and social obligation. The study contributes theoretically by demonstrating how phenomenological approaches illuminate the lived experience underlying electoral behavior, and practically by offering recommendations for candidates, parties, and election administrators engaging identity-conscious constituencies. The research addresses significant gaps in Indonesian electoral studies by centering candidate perspectives and employing phenomenological rigor to analyze local-level identity politics during heightened religious identity mobilization.